¿Cómo se hace un ciclista urbano? - Rojas, Carla (2018)
In this research, the process of formation and consolidation of Cicloaxion as an organization will be developed as a central theme. When analyzing this, two key processes were identified. Before doing so, it is important to mention that they are not two temporally separated processes, but rather interrelated and integrated. Initially, the current members identify, through their own experiences, an individual problem around urban cycling, pointing out causes of the cycling problem as well as envisioning solutions. Then, the organization arises, so the problem is politicized through the identification of campaigns, choice of repertoires, strategies to deal with the matter, use of international and local networks. Finally, an identity is generated among the members. In this way, Cicloaxion is consolidated as an organization within a social movement.